Analisis Kualitas Layanan Menggunakan Framework ITIL V3 Domain Service Operation Website Akademik - Muhammad Asfari Alkaromi; Akhmal Angga Syahputra; Muhammad Asnafi Alkaromi; Ahnaf Vanning Al Haq; Ito Setiawan (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The advancement of information technology has transformed the management of academic systems in universities, necessitating effective and efficient IT management to support operational and administrative processes. Universitas Amikom Purwokerto uses a web-based academic system to integrate academic and administrative services. However, issues such as server connection failures often disrupt operations. Based on an ITIL V3 analysis, the system is at Maturity Level 3 (*Defined*) in problem management, with recommendations to improve real-time monitoring and process flexibility. Implementing these recommendations is expected to enhance service quality and user experience. This study aims to analyze the service quality of Universitas Amikom Purwokerto’s academic system within the service operation domain, particularly in the problem management subdomain. According to the ITIL V3 framework, the system's maturity is at the *Defined* level (Level 3), indicating that problem-handling processes are well-documented but limited in flexibility. These findings highlight the need for improvements in real-time monitoring, predictive analysis, and user feedback to better meet dynamic needs. Such recommendations are expected to improve operational effectiveness and overall user experience.